Polycentricity and Regional Ocean Governance: Implications for the Emerging UN Agreement on Marine Biodiversity Beyond National Jurisdiction - Gjerde, Kristina M.; Yadav, Siddharth Shekhar (Frontiers in Marine Science, 2021)
The governance of the two-thirds of the world’s ocean in areas beyond national jurisdiction (the high seas and deep seabed beyond national jurisdiction or ABNJ) is currently fragmented into diverse institutions addressing specific activities, issues or regions. This has hampered the international community’s ability to redress critical issues including biodiversity loss, pollution, climate change, ecosystem degradation and declining fisheries in an integrated and ecosystem-based manner. Our analysis of polycentricity theory and associated enabling conditions shows that the current polycentric approach to marine biodiversity in ABNJ is not yet fully functional: it is missing the two key attributes of: (1) generally applicable rules and norms structuring actions and behaviors, and (2) processes to enhance cooperation, coordination, and conflict resolution. Based on the enabling conditions conducive for achieving “a functional polycentric governance system” identified in Carlisle and Gruby (2019), combined with a prior analysis applying resilience principles for socio-ecological systems to ABNJ (Yadav and Gjerde, 2020), this article suggests seven ways the emerging United Nations agreement on the conservation and sustainable use of marine biodiversity of ABNJ (BBNJ Agreement) could stimulate coordinated and integrated action at both global and regional levels in ABNJ. These include: (1) overarching rules, goals and objectives; (2) formal and informal conflict resolution mechanisms; (3) robust global institutional arrangements; (4) strengthened global, regional and sectoral bodies with shared and overlapping responsibility for biodiversity conservation; (5) strengthened cooperation through integrated ecosystem assessments and strategic action programmes at ecologically meaningful scales that could include areas within and beyond national jurisdiction; (6) learning exchange mechanisms within and across regions; and (7) strengthened regional and national capacities for ecosystem-based management in ABNJ. Taken together, these tools could enhance the resilience of ocean institutions, ecosystems and biodiversity to cope with growing pressures, uncertainty and rapid change in ABNJ.